The effect of audit fees on disclosure quality in Jordan - Mohammad Ziad Shakhatreh; Safaa Adnan AlSmadi; Ahmad Alkhataybeh (Cogent Business & Management, 2020)
Disclosure quality is a matter of great importance in the accounting literature. This study examines the effect of audit fees, audit firm size and audit opinion on the quality of disclosures. It focuses on a sample of low-quality financial statements in Jordan that have been reported as breaches by the Jordanian Securities Commission (JSC). Data were collected from the financial statements of the manufacturing and services companies listed on the Amman Stock Exchange (ASE) during the period 2009 to 2016. The logistic regression results suggest that audit fees have a positive significant effect, while audit opinion has a negative significant effect on actual violations. However, audit firm size was found to be insignificant in relation to the level of violations.
Keywords: M40; M41; M42; 650; audit fees; audit opinion; disclosures quality